1980
DOI: 10.1111/j.1365-2621.1980.tb07541.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Frozen Storage on Functionality of Meat for Processing

Abstract: Frankfurter quality was monitored to evaluate effects of frozen storage on meat components. After fresh meat controls were tested, beef, pork, and pork fat were frozen and stored at -17:8"C for l-37 wk. At 6-wk intervals, functional and quality tests were performed on thawed and control meat samples and on frankfurters made from the samples. Frozen storage significantly affected beef and pork lean (drip loss, % solids and N in drip, extractable protein, water binding, emulsifying capacity) and fat (beef-thioba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
74
0
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(86 citation statements)
references
References 27 publications
9
74
0
3
Order By: Relevance
“…These thawing methods are time consuming and require external heating, after which change in the quality of the meat occur (Kang et al, 2007). Changes which take place during the thawing processes of frozen meat include the growth of microorganisms, weight loss due to drip loss, and color change (Berry, 1994; Kondratowicz et al, 2008), effect of WHC (Miller et al, 1980;Sebranek, 1979;Zhuang, 2012), increase of rancidity (Lannari and Zaritzky, 1991;Sebranek et al, 1978), denaturation of protein (Wagner and Anon, 1985;Wagner and Anon, 1986) and softening of tissues, which results in a changes which are quite apparent to the consumer (Fennema, 1973;Jason, 1974;Kim et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…These thawing methods are time consuming and require external heating, after which change in the quality of the meat occur (Kang et al, 2007). Changes which take place during the thawing processes of frozen meat include the growth of microorganisms, weight loss due to drip loss, and color change (Berry, 1994; Kondratowicz et al, 2008), effect of WHC (Miller et al, 1980;Sebranek, 1979;Zhuang, 2012), increase of rancidity (Lannari and Zaritzky, 1991;Sebranek et al, 1978), denaturation of protein (Wagner and Anon, 1985;Wagner and Anon, 1986) and softening of tissues, which results in a changes which are quite apparent to the consumer (Fennema, 1973;Jason, 1974;Kim et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Jo et al (2014) found that the WHC of muscle freezing/thawing treatment is lower than that of fresh controls, and this is in accordance the findings of this study. Miller et al (1980) noted that the WHC percentage decreases for pork and beef meat because of damage to the muscle tissue from being frozen. Ngapo et al (1999) showed that damaged cell membranes cause the drip exudate from the intracellular space to the extracellular space, which results in the easy release of drips from the muscle tissue.…”
Section: Water-binding Propertiesmentioning
confidence: 99%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License products (Miller et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…기존 국내의 한우육 관련 연구는 한우육의 품질 구명 Kim and Lee, 2003;Moon et al, 2006;Rhee and Kim, 2001;Park et al, 2002)과 수입육 에 대비하여 한우육의 육질 및 상강도 등이 우수하며 맛 성분 함량이 높다는 (Hwangbo et al, 2001;Park et al, 1994;Yang et al, 2007;Lee et al, 2009) (Winger and Fennema, 1976;Yamamoto and Samejima, 1977;Miller et al, 1980). (Bendall, 1978).…”
unclassified